A computational approach to understanding the deNOₓ properties of Rhodium metal - Carey, John J. (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
The emission of nitrogen oxides (NOx, x = 1, 2) from combustion engines is a significant contributor to acid rain, smog and the enhanced greenhouse effect. The environmental damage these polluntants have caused, as well as human health concerns, has led to governmental regulations aimed at reducing NOx emissions. As the decomposition of NOx gases (deNOx) is difficult due to a high activation barrier, and catalytic technologies have been developed to assist in their subsequent breakdown. These technologies use rhodium, palladium and platinum precious metals employed on oxide suppports. where 111 facets are the dominant surface on the metal clusters. Rhodium is known to be the most effective metal for NOx reduction flue to facile breaking of the NO bond; however, it is becoming increasingly scarce and thus progressively more expensive to use. This has led to significant interest in rhodium free technologies, motivating research to develop alternative, more cost effective catalysts that emulate the reductive properties of rhodium. The need to understand the properties of rhodium metal takes initial precedence before investigating the developent of novell catalysts. Firstly, density functional theory (DFT) will be used to investigate the adsorption of N, O, N2, O2 and NOx to determine the most stable adsorption modes on the {111} surface of rhodium. Their electronic structure on interaction with the rhodium surface will be investigated using partial (ion and l-quantum number decomposed) electronic density of states (PEDOS), charge density and Bader analysis, and compared to the calculated electronic structure of their gaseous species. The energetics of the most stable adsorption modes, and of their gaseous species, will then lbe used to develop a deNOx profile for rhodium.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin